Analisis Strategi Bisnis dan Pengembangan Usaha Emping Singkong RI&CI PT. Sinar Utami Group - Ila Karmila; Gustina Hidayat; Fadila Nurfauzia (MOTIVASI, 2025)
Purpose- The study focuses on analyzing the business strategy and development of RI&CI’s cassava emping under PT. Sinar Utami Group using IFAS, EFAS, and IE matrices. Internally, the business shows strengths in strong commitment, consistent product quality, and sufficient labor availability, but faces weaknesses such as limited promotion, reliance on traditional production methods, raw material supply challenges, and basic financial management. Externally, the business benefits from government support, technological advancements, and expanding markets, while also confronting threats including product imitation, raw material price volatility, and weakening consumer purchasing power. Design/methodology–This study employs a qualitative descriptive approach using a case study method to analyze the business strategy and development of cassava chips (emping singkong) under the RI&CI. Data were collected through in-depth interviews, direct observation, and documentation. Informants were selected using purposive sampling, focusing on individuals directly involved in business operations. Findings - The IFAS and EFAS analyses yielded scores of 3.040 and 2.764, positioning PT. Sinar Utami Group in Quadrant II of the IE Matrix, which suggests a growth strategy. Accordingly, the company should strengthen digital promotion, pursue product innovation, expand its distribution networks, and enhance production efficiency as well as financial management to ensure sustainable development. This study thus offers a comprehensive view of strategic measures that MSMEs can adopt to remain competitive in dynamic business environments.